Kritik Atas Kitab Al-Maghazi Karya Ma’mar Ibn Rasyid Terhadap Konstruk Penulisan - Batu, Anugrah Eran (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2021)
Arguments that Ma’mar is the figure responsible for the organisation of the book of Al-Maghazi, apparently ignore the construction of writing and unreasonable. this study aims to critique the systematic writing of the book of Al-Maghazi by Ma’mar ibn Rashid. There are at least two questions asked, (1) what are the factors that influence Ma’mar ibn Rashid in writing the book of Al-Maghazi, (2) how Ma’mar ibn Rashid's efforts in writing the book of Al-Maghazi. In answering the research problem, the researcher used a qualitative method with the type of literature study research. This study concludes that, First, the general factors that usually influence historical works are: original sources, writing objectives, ideology and personal views, historical context, the interests of the people, historical methods, cultural and linguistic influences, support or encouragement from colleagues or religious authorities, access to writing sources and the influence of other cultures and civilisations. Secondly, possible efforts were also made by Ma’mar ibn Rashid in writing the book of Al-Maghazi, namely: research and collection of sources, verification of authenticity and reliability of the narrative, analysis and selection of information, writing in historical style, structure and organisation, cultural influences and literary norms, purpose of publication, use of diverse sources, compilation of chronology, consideration of religious values and norms, criticality and objectivity, and contribution to Islamic history. Third, the content of the book begins with the story of the digging of the Zamzam well and ends with the story of Fāṭimah's marriage.